Inno-Hortech Cutter / Muhammad Fakhrurrodhi Zainal Ashirin...[et.al] - Ramli, Muhammad Razif; Saidi, Ahmad Baihaqi; Zakaria, Muhammad Nabil Zafran; Mahamat, Arif Afendi (Faculty of Plantation and Agrotechnology, 2017)
Agricultural Machineries Enterprise was established on January 2017 by six (6) of members through partnership. After planning, organizing and generating the ideas, we were register the company under Suruhanjaya Syarikat Malaysia (SSM) and started from that our company was running the business in 01 March 2017. The partnership of company are Muhammad Fakhrurrodhi bin Zainal Ashirin as a General manager, Muhamad Haika bin Jafrias, a Administrative manager, Muhammad Razif bin Ramli as a Operation manager, Ahmad Baihaqi bin Saidi as a financial manager, Arif Afendi bin Mahamat and Muhammad Nabil Zafran bin Zakaria as a Marketing manager. The location of this business is located at No.2A, Jalan Ayer Songsang, Kg Mantai Nyalas, 77000 Jasin, Melaka.